Microsurgery : From Basic Skill of Plastic Surgery to The Top of Reconstruction Ladder - Atmodiwirjo, Parintosa (Lingkar Studi Bedah Plastik Foundation, 2013)
For more than 5 decades, microvascular surgery has been growing and found its place in reconstructive surgery. In Indonesia, microsurgery became popular since 30 years ago. In the past, this subspecialty was developed for soft tissue transfer and replantation of amputated extremities.